The Construction of Early Childhood Responsibility in Recognizing Personal Needs through Toilet Training Habits in Early Childhood Education Institutions (PAUD) - Nugraheni Hery Setyarini; Diah Wahyuningsih (Manunggal Halim Jaya, 2026)
This study aims to analyze the development of responsibility in early childhood in recognizing their own needs through the habituation of toilet training in early childhood education institutions. The study uses a qualitative approach with a case study method conducted on 10 children aged 4–5 years at TK Negeri Pembina, Pringkuku District. Data were collected through observations and interviews with the principal, teachers, and parents. The data were analyzed using data reduction, data display, and conclusion drawing, supported by source and technique triangulation. The results show that structured and consistent toilet training can develop children’s responsibility in recognizing their own needs. Children begin to demonstrate the ability to recognize bodily signals, express their needs, and independently go to the toilet. Supporting factors include teacher consistency, a conducive environment, and collaboration with parents. Meanwhile, inhibiting factors include differences in parenting styles and a lack of consistency in habituation at home. Therefore, toilet training not only plays a role in fostering independence but also serves as an effective means of building responsibility in early childhood.